DSM generation with bistatic TanDEM-X InSAR pairs and quality validation in inclined topographies and various land cover classes - Sefercik, Umut Güneş; Buyuksalih, Gurcan; Atalay, Can (Springer Heidelberg, 2020)
In 2007, synthetic aperture radar (SAR) imaging was modified by TerraSAR-X (TSX); this second-generation SAR satellite offers up to 1 m of spatial resolution. The satellite is capable of interferometric SAR (InSAR), which permits the generation of digital surface models (DSMs). TSX was designed for monostatic InSAR imaging, but the potential for acquired DSMs is limited due to the disadvantages of repeat-pass InSAR geometry under the influence of temporal and related spectral decorrelations. In 2010, TanDEM-X (TDX) was launched to operate in a synchronized helix orbit with TSX to achieve high-quality DSMs covering almost the entire World in the basis of bistatic SAR imaging. In this paper, we focused on the DSM potential of TDX InSAR pairs in inclined topographies, and open, built-up, and forest land cover classes. A 5-m gridded TDX DSM was generated by interferometric processing and comprehensively analyzed by using model-to-model comparison approaches utilizing a reference airborne laser scanning (ALS) DSM. Absolute and relative vertical accuracies were estimated separately for all land cover classes using standard deviation and normalized median absolute deviation considering the influence of terrain tilt. Coherence with the reference DSM was determined by vertical profiles and frequency distribution graphics of height differences. Inaccurate regions were visualized by the generation of height error maps (HEMs). During the analysis, the qualities of the generated 5-m TSX DSM and a freely available 1-arcsecond (similar to 30 m) Shuttle Radar Topography Mission (SRTM) DSM were validated and compared with TDX.
Keywords: TanDEM-X; TerraSAR-X; SRTM; Bistatic; DSM; Quality